Allele-specific gene expression uncovered. - Knight, J (2004)
Genetic variation in populations can result in variation in levels of gene expression but the extent to which this occurs has been unclear. In this article, recent studies of allele-specific expression among autosomal non-imprinted genes are reviewed. These new data provide evidence that differential expression is relatively common and that allelic differences are heritable and can be highly context specific.